Discovery of an ultra-diffuse galaxy in the Pisces-Perseus supercluster - Martínez-Delgado, David; Grebel, Eva K. (Arxiv, 2016)
We report the discovery of DGSAT I, an ultra-diffuse, quenched galaxy located 10.4 degrees in projection from the Andromeda galaxy (M31). This low-surface brightness galaxy (mu_V = 24.8 mag/arcsec), found with a small amateur telescope, appears unresolved in sub-arcsecond archival Subaru/Suprime-Cam images, and hence has been missed by optical surveys relying on resolved star counts, in spite of its relatively large effective radius (R_e(V) = 12 arcsec) and proximity (15 arcmin) to the well-known dwarf spheroidal galaxy And II. Its red color (V-I = 1.0), shallow Sersic index (n_V=0.68), and the absence of detectable H-alpha emission are typical properties of dwarf spheroidal galaxies and suggest that it is mainly composed of old stars. Initially interpreted as an interesting case of an isolated dwarf spheroidal galaxy in the local universe, our radial velocity measurement obtained with the BTA 6-meter telescope (V_h=5450 +/- 40 km/s) shows that this system is an M31-background galaxy associated with the filament of the Pisces-Perseus supercluster. At the distance of this cluster (~78 Mpc), DGSAT I would have an R_e ~ 4.7 kpc and M_V ~-16.3$. Its properties resemble those of the ultra-diffuse galaxies recently discovered in the Coma cluster. DGSAT I is the first case of these rare ultra-diffuse galaxies found in this galaxy cluster. Unlike the ultra-diffuse galaxies associated with the Coma and Virgo clusters, DGSAT I is found in a much lower density environment, which provides a fresh constraint on the formation mechanisms for this intriguing class of galaxy.